Mapping Cyber-Enabled Crime: Understanding Police Investigations and Prosecutions of Cyberstalking - Brianna O'Shea; Nicole L. Asquith; Jeremy Prichard (International Journal for Crime, Justice and Social Democracy, 2022)
Stalking is one of the main types of abusive behaviour facilitated by technology. The purpose of the current study was twofold: to identify the challenges of cyberstalking investigations and prosecutions in Australia and determine how best to investigate these types of offences. A qualitative analysis of four years of interviews, focus groups and participant observations with police departments provides an overview of the cyberstalking investigative process. The findings map out the process from the initial report of the incident to the preparation of the prosecution brief. This analysis positions cyberstalking investigations as an interesting case study in the midst of increased scrutiny about the way that police investigate technology-facilitated abuse.